Social isolation during the covid-19 pandemic impaired vitamin d concentrations, motor performance and physical fitness in adolescents - Frederico Bento de Moraes Junior; Maiara Cristina Tadiotto; Patricia Ribeiro Paes Corazza; Francisco Jose de Menezes-Junior; Caroline Brand; Jorge Mota; Neiva Leite (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to verify the effect of social isolation arising from the Coronavirus pandemic (COVID-19) severe acute respiratory syndrome (SARS-CoV-2) on vitamin D (25(OH)D) concentrations, motor performance, and cardiorespiratory fitness (CRF) in adolescents. This research method is Case-control study, which included 34 boys, aged 12-16 years. In the pre-pandemic period, 17 schoolchildren were evaluated in December 2019, classified according to body mass index Z-score (BMI-z) as: eutrophic (n=8) and overweight (n=9). The post-pandemic group was composed of 17 boys, evaluated in March 2022, matched with the same BMI-z characteristics. Stature, body mass, fat mass (FM), fat free mass (FFM), flexibility (FLEX), 25(OH)D, absolute CRF (CRFabs) and relative (CRFrel) were assessed. The Supine-to-Stand test (STSTIME) execution time was used to assess motor performance and motor competence by the motor patterns used in execution (STSMC). considering p<0.05 significant. The results showed that, post-pandemic, there were impairment on 25(OH)D, FLEX, STSTIME e CRF (p<0.05). Both eutrophic and overweight groups reduced 25(OH)D concentrations (p<0.001) and increased STSTIME (p=0.02) but did not modify STSMC. Regarding CRF, eutrophic individuals showed lower CRFabs and CRFrel values (p≤ 0.005), however no changes in the overweight group. We conclude that social isolation impaired the 25(OH)D concentrations and motor performance of adolescents. However, it stands out that the eutrophic were the most impacted with social isolation, as they showed unfavorable effect also on CRF.